Adjunctive individual meaning-centered psychotherapy plus protocolized fluoxetine for moderate-to-severe adolescent depression - Sheng, Li-Li; Zhang, Min (Frontiers in Psychiatry, 2026)
ObjectiveTo determine whether individual, adapted Meaning-Centered Psychotherapy (IMCP), delivered alongside protocolized fluoxetine, improves depressive symptoms and related outcomes in adolescents with moderate-to-severe depression.MethodsAmong 168 adolescents with DSM-5-TR depressive disorder and Patient Health Questionnaire–9 modified for Adolescents (PHQ-A) ≥10, all receiving protocolized fluoxetine, participants were randomized to IMCP+TAU or TAU; the IMCP group completed seven weekly 60-minute sessions. The primary outcome was PHQ-A; secondary outcomes were the Zung Self-Rating Anxiety Scale (SAS), Clinical Global Impressions - Severity and - Improvement (CGI-S/CGI-I), Children’s Global Assessment Scale (CGAS), Rosenberg Self-Esteem Scale (RSES), and Meaning in Life Questionnaire - Presence and Search subscales (MLQ-Presence/Search). Serious adverse events (SAEs) and adverse events (AEs) were recorded throughout the 12-week study period.ResultsAcross 12 weeks, the IMCP group showed earlier and larger reductions in depressive symptoms (PHQ-A) than TAU, with advantages evident by week 4 and maintained at weeks 8 and 12; severity distributions shifted more toward milder categories in IMCP. Anxiety (SAS) declined in both groups, with greater improvement in IMCP. Clinician ratings reflected the same pattern: IMCP achieved lower illness severity (CGI-S) and better early improvement (CGI-I), and greater functional gains (CGAS) throughout follow-up. Self-esteem (RSES) rose more in IMCP. Meaning in life-Presence (MLQ-Presence) increased more with IMCP, while Search (MLQ-Search) changed minimally and similarly across groups. Neither group experienced SAEs, and AE frequencies were low and did not differ meaningfully between groups.ConclusionsAdjunctive IMCP with standardized fluoxetine produced greater 12-week improvements than TAU in symptoms, clinician ratings, functioning, self-esteem, and felt meaning, supporting IMCP as a feasible and effective adjunct.